The political ontology of Giorgio Agamben : signatures of life and power - Primera, German Eduardo (New York : Bloomsbury Academic, 2019)
"With the publication of The Use of Bodies (2016) Agamben's multi-volume Homo Sacer project has come to an end, or to paraphrase Agamben, has been abandoned. We now have a new vantage point from which to reread Agamben's corpus; not only his method but his political and philosophical thought can been seen in a clearer light. This timely book both assesses and contributes to the debates on the Homo Sacer project in its entirety. Rethinking the notions of life and power - two of the central themes in Agamben's work - through a reconstruction of his philosophical method and the examination of his critique of Western metaphysics, this book argues that Agamben's thought cannot be fully grasped if we do not account for the intertwining of politics and ontology. This book argues that it is only by revisiting Agamben's critique of signification and metaphysics and examining his reconstruction of the archaeological method that we can understand his notions of life and power. By bringing together the two parts of the Homo Sacer project, the archaeology of the signature of Sovereignty and the archaeology of governmentality, this book provides an analysis of the production of Agambenian 'bare life'. In this sense this project re-articulates Agamben's works on signification, language and ontology with his archaeology of power. Offering an original examination of Agamben's notion of resistance, this is essential reading for any thoughtful consideration of his philosophical legacy"--
Paradigms, signatures, and philosophical archaeology -- Language and being: the work of signatures -- The paradox of sovereignty: bare life and its paradigms -- The signature of power: economic theology, government and bare life -- Neoliberalism, governmentality, and sovereignty: the lessons of the kingdom and the glory -- The signature of life: the meaning of biopolitics -- The politics of inoperativity: suspending the signatures of life and power.
Includes bibliographical references and index.
Keywords: Agamben, Giorgio, -- 1942-; Ontology; Power (Philosophy); Political science -- Philosophy; Ontology; Power (Philosophy); Agamben, Giorgio, 1942-; Political science--Philosophy